Hubungan Pengetahuan dan Persepsi terhadap Minat Kepesertaan BPJS Ketenagakerjaan pada Pedagang di Pasar Badung Kota Denpasar - Damayanti, Luh Made Mira; Arjawa, I Gst Putu Bagus Suka; Zuryani, Nazrina (Socio-political Communication and Policy Review, 2024)
This research aims to predict factors related to interest in BPJS Employment participation among market traders using knowledge and perception variables. This type of research is quantitative research using data obtained from the method of distributing questionnaires to 90 respondents, namely traders at Badung Market, Denpasar City with slovin calculations in determining the sample. The data analysis techniques used are Pearson Correlation and Multiple Linear Regression. The results of the correlation test show between knowledge and interest in participation is 0,579, which has a medium level of correlation, and between perception and interest in participation is 0,561, which also has a medium level of correlation. Then, the results of the coefficient of determination (R2) show that the participation interest variable can be influenced by knowledge and perception variables as much as 40,1%, while the remaining 59,9% is influenced by other variables outside the research. Furthermore, the results of the t test show that the tcount value of the knowledge variable is 3,849, which shows that Ho1 is rejected and Hk1 is accepted, meaning that knowledge has a positive and significant effect on partial interest in participation. The tcount value for the perception variable is 3,417, which shows that Ho2 is rejected and Hk2 is accepted, meaning that perception has a positive and significant effect on partial participation interest. Finally, the results of the F test show that the Fcount value is 30,739, which shows that Ho3 is rejected and Hk3 is accepted, meaning that knowledge and perception have a positive and significant effect on participation interest simultaneously.